Views of Erasmus+ Exchange Students Studying in the Field of Sports in Different Countries Regarding the Programme - Zeynep Onağ; Diyar Kaya Saylam; Emine Kaya (Journal of Educational Issues, 2024)
This study aims to analyze the views of Erasmus+ Exchange students studying in the field of sports in different countries regarding the programme. In the study, descriptive phenomenology design, one of qualitative study designs, was used. In accordance with this aim, five open ended questions answered by 14 foreign students participating in the Erasmus+ exchange programme in different universities offering sports science programmes in Portugal were analyzed through content analysis. The data obtained from the students were discussed under five themes, which are; reasons for participating in the programme, contribution to the field, challenges faced, similarities and differences with their education and suggestions. The views expressed by the students reveal that their reason for participating in the programme is to experience different cultures; the contribution of the programme to their field is the different course styles; the challenges they face are language and financial challenges; the similarity with the education in their country is the course contents and the difference is the teaching styles; and their suggestion is that the students shouldn’t be afraid to participate in exchange programmes.